Automatically generating assembly sequences with an ontology-based approach. Issue 2 (10th December 2019) - Zhong, Yanru; Jiang, Chaohao; Qin, Yuchu; Yang, Guoyu; Huang, Meifa; Luo, Xiaonan
Abstract : Purpose: The purpose of this paper is to present and develop an ontology-based approach for automatic generation of assembly sequences. Design/methodology/approach: In this approach, an assembly sequence planning ontology is constructed to represent the structure and interrelationship of product geometry information and assembly process information. In the constructed ontology, certain reasoning rules are defined to describe the knowledge and experience. Based on the ontology with reasoning rules, the algorithm for automatically generating assembly sequences is designed and implemented. Findings: The effectiveness of this approach is verified via applying it to generate the assembly sequences of a gear reducer. Originality/value: The main contribution of the paper is presenting and developing an ontology-based approach for automatically generating assembly sequences. This approach can provide a feasible solution for the issue that mathematics-based assembly sequence generation approaches have great difficulty in explicitly representing assembly experience and knowledge.